Lamto GIS layer (raster dataset): orthomosaic of aerial photographs of the Lamto reserve (Côte d'Ivoire) acquired by IGN in 1963 - Zaiss, R.; Gignoux, J.; Konaté, S.; Barot, S. (DataSuds, 2022)
This dataset holds the process chain to produce a orthomosaic from 220 aerial photographs acquired by IGN in 1963 under the mission AOF 566P5000. The dataset covers the Lamto reserve. We orthorectified the scanned images using ground control points from Google Maps and a structure from motion software (SfM). This dataset contains the scanned aerial photographes, the ground control points and the finale orthomosaic with a 17 cm ground resolution.